Legal Principles of Environmental Protection in the European Union - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Legal principles represent general guidelines under which a positive law should be created. The policy of the European Union should contribute to preservation, protection and improving of the quality of environment, health protection, and rational use of natural resources. One of the main objectives of the environmental policy is a sustainable development. The EU institutions should also be governed by principles of subsidiarity and integration, precautionary principle, prevention principle, principle of rectification of damage at source and polluter-pays principle. The European Union tries to find the balance between economic progress and sustainable development and in that process the mentioned environmental principles play an important role.